The Effect of Halal Supply Chain Management on the Sustainability Performance of Food SMEs in Padang City - Leidina Zein; Nilda Tri Putri; Alizar Hasan; Rika Ampuh Hadiguna; Dicky Fatrias; Dina Rahmayanti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study examines the impact of Halal Supply Chain Management (HSCM) on the sustainability performance of food SMEs in Padang City, evaluating consumer trust as a mediator and Lean Green Practices as a moderator. Driven by low halal certification rates despite rising consumer demand for halal and sustainable products, data were collected from food SME owners using a survey method and analyzed via PLS-SEM.The results reveal that HSCM does not directly affect sustainability performance. However, consumer trust fully mediates this relationship, demonstrating that HSCM drives sustainability performance by fostering consumer confidence in halal integrity and quality. Additionally, Lean Green Practices do not significantly moderate the relationship between HSCM and sustainability performance. Overall, the findings emphasize the necessity for SMEs to build consumer trust and adopt eco-efficient operational strategies to ensure long-term business sustainability. Contribution to SDGs: SDG 3: Good Health and Well-beingSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 16: Peace, Justice and Strong Institutions